Method and apparatus for removing moisture from at least one product - Chong, Gun Hean; Spotar, Sergey (2012)
An apparatus (100) for removing moisture from at least one product, the apparatus (100) includes at least one dryer (105) having at least one adsorbent desiccant therein for drying, a gas source (110) in fluid communication with the at least one dryer (105) having the at least one adsorbent desiccant therein for drying and extracting moisture from gas supplied by the gas source (110) to produce a dried gas, at least one heater (115) to raise temperature of the dried gas blown into at least one drying chamber (120) for drying the at least one product and at least one level control element (125) that closes to complete an electrical circuit when sensing a predetermined level of flow pressure of the dried gas is sufficient for maintaining proper drying operation.